Igniting the Caribbean's past : fire in British West Indian history - Richardson, Bonham C., 1939- (University of North Carolina Press, 2004)
Exploring the effects of fire in the social and ecological history of the British Lesser Antilles, this title focuses on the late 19th century, leading to the 1905 withdrawal of British military forces from the region. It shows how fire-lit social upheavals served as forerunners of political independence movements.